Sosialisasi Strategi Pemasaran Melalui Media Sosial Pada UMKM Pedagang Sayur Cilacap - Yusuf, Dede; Nuni Wulansari; Zulfikar Yusya Mubarak; Tri Kusuma Wardani; R. Bagus Bambang Sumantri (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2025)
The development of communication technology and social media in Indonesia, where 96% of internet users use social media, has changed the way of marketing, including for small and medium enterprises (SMEs). Information literacy is an important skill to use information ethically and efficiently in planning and implementing empowerment programs. This community service activity aims to provide insight into marketing strategies through social media to vegetable traders in Cilacap who often face budget constraints. Social Media Marketing (SMM), which has been proven to increase sales for 74% of SMEs that implement it, was chosen as a flexible strategy to increase sales through platforms such as Facebook and Instagram. In addition to SMM strategy training, participants were also given branding designs in the form of banners and logos to increase the appeal of their products. Based on the results of the socialization, participants understand the importance of digital marketing and branding, which is expected to help local SMEs optimize their budgets for more sustainable business growth.